MENINGKTKAN MOTIVASI BELAJAR MAHASISWA KEPERAWATAN MELALUI METODE PEMBELAJARAN COOPERATIVE LEARNING - Puspita, Sylvie; Triana, Neny (IJNP (Indonesian Journal of Nursing Practices), 2015)
One of factors that determine student success in learning is the selection of appropriate learning method. Learning methods that are not boring for the students is one learning method that can improve student learning motivation that ultimately might improve student achievement. Cooperative learning is one of the methods that can be applied. The division of a group of shared characteristics of students are the hallmark of this learning method. This study aimed to do a review article to know the eff ectiveness of learning cooperative learning to enhance student motivation to expect any impact rising encountered during the learning process of cooperative learning. A search the article in Proques on articles related to cooperative learning on student motivation by keyword «eff ects of cooperative learning on student motivation and achievment» found 3079 articles selected then the 2010- 2015 with the same keywords «eff ects of cooperative learning on student motivation and achievment «is found 543 then we select the article to 15 articles. Cooprerative learning is one method that can be applied in the learning nursing process. An increase in student motivation in learning have a positive impact on the achievement of the mahasiswats. Obstacles are often encountered any member of the group who did not participate in the task. The efectifi tas cooperative learning on student learning motivation that impact on achievement.Keywords: Cooperative learning, motivation to learn, student achievement